2002
DOI: 10.1021/ol0269289
|View full text |Cite
|
Sign up to set email alerts
|

(R)-2,4-Dihydroxybutyramide seco-Pseudonucleosides:  New Versatile Homochiral Synthons for Synthesis of Modified Oligonucleotides

Abstract: Two series of seco-pseudonucleoside synthons were synthesized from (R)-(+)-r-hydroxy-γ-butyrolactone and (R)-(−)-pantolactone by aminolysis, side-chain protection, dimethoxytritylation, and phosphitylation or solid-phase attachment. The phosphoramidites and solid supports were used in automated DNA synthesis to prepare oligonucleotides modified with one or more 2,4-dihydroxybutyramide units bearing side-chain reporter groups. These new oligonucleotide modification reagents allow the introduction of a label int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 32 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…To allow structural studies, we chose to use a pantolactone-based ribose mimic developed by Dioubankova et al (2). This synthetic route was used to extend our studies on metal-assisted hybridization of oligonucleotides, providing an easy way to increase nucleic acid duplex stability.…”
Section: Introductionmentioning
confidence: 99%
“…To allow structural studies, we chose to use a pantolactone-based ribose mimic developed by Dioubankova et al (2). This synthetic route was used to extend our studies on metal-assisted hybridization of oligonucleotides, providing an easy way to increase nucleic acid duplex stability.…”
Section: Introductionmentioning
confidence: 99%
“…α,γ‐Dihydroxy acids and amides such as 27 and 28 are precursors of β,β‐disubstituted γ‐butyrolactones that are analogs of pantolactone 14. Such lactones provide synthetic pantothenamides ( N ‐modified α,γ‐dihydroxy amides) by aminolysis 15. Recent studies16 have shown that the biological activity of pantothenamides depends on the substitution at, and the configuration of, the quaternary carbon atom.…”
Section: Resultsmentioning
confidence: 99%
“…CPG supports for solid-phase oligonucleotide synthesis loaded with the corresponding ligand-containing linkers PyS (96.1 µmol/g), PyL (60.1 µmol/g), PEPy (44.1 µmol/g), BPEA (35.0 µmol/g), and Per (29.9 µmol/g) were obtained according to guidelines in the literature [24]. The PyS linker (N-(1-pyrenemethyl)-( S )-2,4-dihydroxybutyramide) was synthesized as described previously [17,25]. The PyL linker was prepared as described in reference [18].…”
Section: Methodsmentioning
confidence: 99%